The availability of programs and methods of preventive awareness in Algerian institutions the analysis of some previous studies that dealt with it - Abdelhak Souilem; Mohammed Safi (Social Empowerment Journal, 2023)
This study aims to try to identify the extent of the availability of programmers and techniques of preventive awareness of occupational risks that achieve industrial security in Algerian institutions. This is done through analyzing some of the previous studies that dealt with it and searching the results of those studies about the effectiveness and achievement of:- Systems and prevention regulations of occupational risks that achieve industrial security.- Providing means of protection against occupational risks that achieve industrial security.- Providing health services and guidance programs that achieve industrial security.               This topic is considered one of the most important topics that aim at protecting workers in the               workplace as they are considered the main pillar for upgrading the level of the institution. This is all to boost the culture of occupational security and health in various fields of work, The study reached a set of results and the most prominent of which were the following:- The majority of specialists and engineers are not performing their tasks that they are supposed to do through their tendency to the administrative side and forgetting the field side.